(untitled) (Journal of Comparative & International Higher Education, 2022)
The Thousand Talents Plan was an ambitious government initiative to repatriate and/or recruit experts from the global Chinese diaspora, along with some non-Chinese experts, with generous research funding and relocation packages. The plan has received much criticism from abroad, accusing endeavors of taking advantage of the open international education sector and facilitating espionage. While the Thousand Talents Plan received much of the attention, there are reportedly over 200 talent recruitment plans implemented by the Chinese government. We refer to these Talents Plans broadly as the Thousand Talents Brand (TTB), due to the diverse subjects, various programs, and a disparate number of the plans. Given the scrutiny and haphazardness of these initiatives, it has been difficult to gauge the impact on the global landscape of higher education, as official data on the broader project has not been readily available. Using bibliometric analysis of Web of Science, we find that research with funding from the TTB did decrease following the recent outcry, but was only roughly 1% of all Chinese research output at its peak in 2018. We find that the research was mostly concentrated in the hard sciences, with relatively little in the social sciences. Our results show the research funded through the initiatives was most commonly partnered with researchers in the Western powers, such as the US, Germany, and England, including connections to institutions with national security concerns like the US Department of Energy. While the findings do illustrate a complex web of global research governance through international partnerships, they cannot alleviate concerns that the TTB programs are potentially malign to sensitive sectors.